2015
DOI: 10.4103/0019-509x.175841
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional profile of pediatric cancer patients at Cancer Institute, Chennai

Abstract: Under-nutrition is present in close to half of the pediatric cancer patients presenting to our institute. Active nutritional intervention and education were able to significantly reduce the prevalence of under-nutrition in patients at the end of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 1 publication
2
18
0
Order By: Relevance
“…Nutritional status starts to deteriorate rapidly after treatment begins and malnutrition continues to be a problem underlining the need to develop efficient methods to provide nutritional support for children with cancer 35 . Two studies reported improvement in nutritional status of the patients during the course of treatment attributed to active nutritional interventions 36,37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional status starts to deteriorate rapidly after treatment begins and malnutrition continues to be a problem underlining the need to develop efficient methods to provide nutritional support for children with cancer 35 . Two studies reported improvement in nutritional status of the patients during the course of treatment attributed to active nutritional interventions 36,37 …”
Section: Discussionmentioning
confidence: 99%
“…35 Two studies reported improvement in nutritional status of the patients during the course of treatment attributed to active nutritional interventions. 36,37 The value of serum albumin and prealbumin for diagnosing or monitoring malnutrition is controversial considering their relatively low specificity and the effects of acute illnesses, especially inflammatory states. [38][39][40] A systematic review reported that serum visceral proteins are not predictive of nutritional deprivation in starved and otherwise healthy malnourished people.…”
Section: F I G U R Ementioning
confidence: 99%
“… 26 Malnutrition is a significant problem in developing countries, and it has been associated with poor outcomes in pediatric malignancies, but it was not a significant prognostic factor in this study. 27 …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of undernutrition in children with cancer varies between 10% and 60%, depending on the criteria and assessment of undernutrition, types and stages of malignancy, the time of assessment during anti-tumor treatment, and the socioeconomic status of the examined patient subset [8,9]. Higher prevalence data of undernutrition have been published from low-GDP countries, where even most healthy children are undernourished [8,10]. In contrast, undernutrition is less frequent and oncological treatment outcome measures are better in high-GDP countries [8,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Higher prevalence data of undernutrition have been published from low-GDP countries, where even most healthy children are undernourished [8,10]. In contrast, undernutrition is less frequent and oncological treatment outcome measures are better in high-GDP countries [8,9,11]. The nutritional status of Hungarian children with malignancies has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%